Canine orchiectomy via scrotal approach using vessel-sealing device: prospective observational study of 200 cases - Yiapanis, C; Ober, C; Psyllaki, M; Attipa, C; Potamopoulou, M; Vasilakis, T; Milram, J (Journal of the Hellenic Veterinary Medical Society, 2024)
Canine orchiectomy involves making an incision in the prescrotal area, exteriorizing both testes via the same incision, ligating the blood vessels and spermatic cord, removing the testes, and suturing the incision. A briefer duration of anesthesia and surgery and decrease of postoperative morbidity could be obtain using a vessel sealing device. The aim of this study was to determine the feasibility and safety of orchiectomy in dogs by a scrotal approach with the use of a vessel-sealing device. Scrotal orchiectomy was performed with the use of monopolar electrosurgery device in pure cutting mode and a vessel-sealing device. Data were collected prospectively for the following categorical variables: breed, age, body weight, lifestyle, surgical time, indications for surgery and complications. No complications were reported in 187 of 200 (93.5%). The complications documented were automutilation (AM), incisional complications (IC) and scrotal complications (SC). AM complications (11/200 [5.5%]) and SC complications (2/200 [1%]) were treated without additional surgery and resolved by day 10 after the surgery. Procedure duration (2,1 minutes± 0.4 minutes) was briefer than traditional castration duration reported in literature (3.5 ± 0.4 minutes). This study provides evidence that canine orchiectomy by scrotal approach with the use of a vessel-sealing device was feasible and safe. Furthermore, it was associated with a low complication rate and had the benefit of reduced surgical time and postoperative morbidity. This technique is promising for widespread application in veterinary surgery to help with haemostasis in canine orchiectomy.